On Solvability of the Matrix Equation AX – XB = C over Integer Rings (Моделювання, керування та інформаційні технології, 2019)
In this communication we present conditions ofsolvability of Sylvester matrix equation AX – XB = C over integerdomains. The necessary and sufficient conditions of solvability ofSylvester equation in term of columns equivalence of matricesconstructed in a certain way by using the coefficients of thisequation are proposed